Characterizing the Somatosensory Profile of Patients With Failed Back Surgery Syndrome With Unilateral Lumbar Radiculopathy Undergoing Spinal Cord Stimulation: A Single Center Prospective Pilot Study. Issue 3 (10th October 2018) - Ramaswamy, Shankar; Wodehouse, Theresa; Langford, Richard; Thomson, Simon; Taylor, Rod; Mehta, Vivek
Abstract : Objectives: Currently little objective evidence exists regarding the phenotype or somato‐sensory profile of patients with Failed Back Surgery Syndrome (FBSS). The aim of this study is to characterize the somato‐sensory profile of the patients with FBSS undergoing spinal cord stimulation (SCS). Methods: A combined quantitative sensory test and questionnaire approach was used to characterize the somatosensory profiles of patients undergoing SCS. Results: Baseline somatosensory profiles were obtained from 23 patients and full three‐month data was obtained from 19 patients. At baseline, there was a high prevalence (>50% prevalence of moderate to severe sensation) of burning, tingling, electric shock, numbness, and pressure pain sensitivity. None of the sensory symptoms were present at significant levels at three months following SCS. At baseline, 65% of patients had an inefficient conditioned pain modulation (CPM). Three months post‐SCS, 95% of patients had an efficient CPM. All the patients who had an inefficient CPM at baseline had a successful implant at three months and their CPM became efficient in all but one patient. Only 50% of the patients with an efficient CPM at baseline, had a successful implant at three months post‐SCS. Conclusion: Although very low numbers, we could demonstrate the somatosensory profiles of patients with FBSS undergoing SCS. Early indication may associate an efficient CPM profile having a higher chance of an unsuccessful implant at three months.